Respuesta :

Answer: x = 1; y = 4

Step-by-step explanation:

2y + 5x = 13

2y - 3x = 5

To be able to use the elimination method, one of 2ys has to be negative

To do that, you multiply one of the equations by -1, you can choose anyone but I chose the second equation.

The system of equations now look like this:

2y + 5x = 13        2y + 5x = 13

(2y - 3x = 5) -1    -2y + 3x = -5

Now you add both set of equations together and get:

8x = 8

Divide both sides by 8

x = 1

Now that we know what x is, we can substitute using one of the equations to find y. I chose the first equation, 2y + 5x = 13

2y + 5x = 13

Substitute x for 1

2y + 5(1) = 13

2y + 5 = 13

Subtract 5 from both sides

2y = 8

Divide both sides by 2

y = 4

Does that help? Hopefully, it does! :3